Interactions between Proteins Encoded within the Human Cytomegalovirus UL133-UL138 Locus - Petrucelli, Alex (American Society for Microbiology, 2012)
We previously described a novel genetic locus within the ULb′ region of the human cytomegalovirus (HCMV) genome that, while dispensable for replication in fibroblasts, suppresses replication in hematopoietic progenitors and augments replication in endothelial cells. This locus, referred to as the UL133-UL138 locus, encodes four proteins, pUL133, pUL135, pUL136, and pUL138. In this work, we have mapped the interactions among these proteins. An analysis of all pairwise interactions during transient expression revealed a robust interaction between pUL133 and pUL138. Potential interactions between pUL136 and both pUL133 and pUL138 were also revealed. In addition, each of the UL133-UL138 locus proteins self-associated, suggesting a potential to form higher-order homomeric complexes. As both pUL133 and pUL138 function in promoting viral latency in CD34(+) hematopoietic progenitor cells (HPCs) infected in vitro, we further focused on this interaction. pUL133 and pUL138 are the predominant complex detected when all proteins are expressed together and require no other proteins in the locus for their association. During infection, the interaction between pUL133 and pUL138 or pUL136 can be detected. A recombinant virus that fails to express both pUL133 and pUL138 exhibited a latency phenotype similar to that of viruses that fail to express either pUL133 or pUL138, indicating that these proteins function cooperatively in latency and do not have independent functions that additively contribute to HCMV latency. These studies identify protein interactions among proteins encoded by the UL133-UL138 locus and demonstrate an important interaction impacting the outcome of HCMV infection.